Assessing the Impact of A Product-Harm Crisis on Brand Trust And Brand Image: A Focus on the Listeriosis Crisis - Siyasanga Mgoduka; Shalen Heeralal (Research Synergy Foundation, 2023)
Brand crises endanger companies, and no organisation is immune from them; each has an equal risk of experiencing one. Existing research on crisis brands lists detrimental consequences on the focus brand and experiments with coping mechanisms. Research on the impact of the brand crisis on brand trust and brand image is sparse. This study examines the impact of a product-harm crisis on brand trust and image. A descriptive quantitative research method was used to collect data from 384 randomly selected food retail store shoppers. The findings revealed that consumers continue to trust open and honest brands during a crisis. The research was limited to uMhlathuze municipality; thus, it cannot be generalised. The brand crisis was limited to the Listeriosis case. The study contributes to the current body of knowledge on brand management by providing insight into how organisations can respond after a crisis to regain their consumers' trust. The research concludes that taking responsibility after a crisis outbreak and being open and honest about the crisis can result in consumers' forgiveness, and they end up overlooking the crisis and its negative impacts.